Policy Socialization and Business Strategy Direction of Eco-Tourism - Miguel Angel Esquivias; Lilik Sugiharti; Hilda Rohmawati; I Made Laut Mertha Jaya (ETIKONOMI, 2022)
This study aims to estimate the losses of tourism-related sectors and businesses to take recovery steps by disseminating policies and strategic directions. This study uses the Seasonal Autoregressive Integrated Moving Average (SARIMA) to calculate losses. This study indicates that the average percentage of losses in the tourism sector from January to August 2020 is 68% (9,508 million USD) to 69% (10,328 million USD). Several sectors experienced losses, especially accommodation (2978 to 3235 million USD); food and beverages (1750 to 1900 million USD); and shopping (1530 to 1662 million USD). Business actors need to know the socialization of government policies such as fiscal stimulus, CHSE (Cleanliness Health Safety Sustainability) certification, and market reactivation. The direction of the right strategy is also carried out, such as product innovation, improvement of health protocols, digitization, and certification. How to Cite:Esquivias, M. A., Sugiharti, L., Rohmawati, H., & Jaya, I.M.L.M. (2022). Policy Socialization And Business Strategy Direction Of Eco-Tourism. Etikonomi, 21(1), 193-212. https://doi.org/10.15408/etk.v21i1.23068.